Hybrid method for benchmarking the operating costs of Brazilian energy distributors - Azevedo de Oliveira, Luís Filipe (2024)
Purpose: This study aims to propose a model for benchmarking evaluation, applied to the Brazilian regulatory system in establishing efficient operating costs for electricity distribution concessionaires. Theoretical framework: The application of data envelopment analysis to the regulation of electrical energy distribution is discussed, elucidating how different regulatory models accompany this modality. Methodology: The proposed methodology is based on a benchmarking evaluation model that integrates the associated use of Data Envelopment Analysis and Stochastic Frontier Analysis, through a methodology that establishes the evaluation of efficiency in Three Stages. Findings: The results of the performance assessment were expressed in terms of management efficiency, in which the effects of the operational environment and statistical noise are controlled, resulting in a rigorous measure of efficiency, by introducing manageable and unmanageable variables into the calculation directly from efficiency. Originality: The methodology allows to adjust operational costs, by levelling the operating environment of each electricity distribution concessionaire before repeating the DEA analysis, making the concessionaires' performance more coherent with the characteristics of the Brazilian market.